SAVI Approach Paper 3: Theory of Change - SAVI (DFID, 2015)
SAVI’s theory of change is a simple, practical guide that staff and pa rtners use to plan and to monitor change – as well as to reflect on an d enhance their own effectiveness. It sets out broad stages of attitud e and behaviour change over time to facilitate effective citizen engag ement in governance processes, systems and structures....